Peak leadership fitness : elevating your leadership game - Tobin, Timothy J. (Association for Talent Development, 2019)
Get leadership-fit and see results in yourself and others. Leadership and fitness are both journeys of self-discovery. Both require self-awareness, passion, and commitment. Both have the potential to inspire others. And for both, results come only with effort. To achieve great heights, you must be willing to take the first step, put in the work, and overcome the inevitable obstacles. In Peak Leadership Fitness: Elevating Your Leadership Game, leadership coach and fitness expert Timothy J. Tobin invites you to share the lessons he's learned at the intersection of physical and leadership fitness. With the encouraging style of a trainer-coach, Tobin shares his four fitness principles: You never know what you're capable of until you take that first step. You must put in the effort. You learn more about yourself when times are tough. What you consume matters. Tobin describes the foundations for leadership fitness, including motivation and mindset, and details his steps to becoming leadership-fit. From taking your pulse to seeking recovery by building endurance, Tobin employs fitness metaphors while remaining aware of the critical difference between personal fitness and leadership--the stakes are much higher with leadership. This book was written for today's and tomorrow's leaders facing today's challenges--time constraints, overcrowded leadership development landscape, and uncertainty about where to start. It is grounded in learning and development and leadership research and illustrated with true-to-life vignettes, sample leadership fitness plans, templates, and tip sheets. Tobin points out the opportunities for leadership development that are all around you--you just need to know where to look and how to integrate the activities into your regular routine. Train smart; train often. Build good habits. Develop yourself and others. You've got this!